PENGARUH KERJA SAMA TIM, KOMITMEN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI PT. INKO ORGANIK JAYA KABUPATEN SITUBONDO - Romadani, Novita Dwi; Arief, Mohammad Yahya; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
At PT. Inko Organik Jaya in Situbondo Regency really needs employees who are committed to improving optimal work and utilization of human resources. And contribute to employee performance. The aim of this research is to analyze and test the influence of teamwork, commitment and work motivation on performance through job satisfaction. This research is quantitative research. The population used in this research was 33 employees of PT. Inko Organik Jaya, Situbondo Regency. The sampling technique uses saturated sampling. Data analysis and hypothesis testing in this research used the Structural Equation Method - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Teamwork has a positive effect on Job Satisfaction, Teamwork has a significant positive effect on Performance, Commitment has a positive but not significant effect on Job Satisfaction, Commitment has a significant positive effect on Performance, Motivation has a significant positive effect on Job Satisfaction, Motivation has a significant positive effect on Performance. The results of the indirect effect hypothesis test show that teamwork on performance through job satisfaction has a positive but not significant effect, commitment to performance through job satisfaction has a significant positive effect, motivation on performance through job satisfaction has a significantly positive effect.